(untitled) (Journal of Contemporary Philology, 2018)
Literary science and comparative literature have developed imagology as a separate disciplinedealing with the study of the images of the Other. The most common form of an image of the Other is the stereotype a term that has found broad use in all social theories during recent decades. The stereotype becomes a means for recognition, labeling, orientation, validation and evaluation. In the history of studying stereotypes, ethnical and cultural stereotypes have received the greatest amount of attention. In our cultural and literary history, a special place is reserved for the stereotypes of Macedonian victims exiled during the Civil War in Greece. In time, and throughout time, the Aegeans and “Aegeanism” in general have received certain ideological contents, transforming them into a myth which can have either positive or negative uses depending on the context. The positive interpretation of that myth can be seen through the preferential treatment of so-called Aegean themes found in the works of renowned artists coming from that part of Macedonia. The negative interpretation can be seen in the factuality of the negative consequences against Aegeans stemming from negative stereotypes about them, such as their alleged unsuitability to do public work, or viewing them as suspicious in certain political contexts.